Teaching and learning in problem solving: algebraic identity - Jiménez Espinosa, Alfonso; Parra Quemba, Laura Emily; Camacho Reyes, Hollman Dubán (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article presents partial results of a research aimed to: establish the characteristics of the practices of teaching and learning in problem solving of algebraic factorization for the eighth grade and characterize some aspects of teaching practices and learning problem solving on algebraic identities. From the analysis of three school texts and a questionnaire applied to 191 students, the epistemic and cognitive configuration of the Ontosemiotic Approach is made. The components of epistemic, cognitive and affective suitability of the approach give relevance to the degree of representativeness of the institutional meaning, to the appropriation of knowledge and to the use of technological means. The methodology was of a mixed nature, and the content analysis method was used. Among the findings it is inferred that the traditional pedagogical model prevails, because the algebra classes are based on the explanations of the teachers.